AKTIVITAS ANTIBAKTERI EKSTRAK METANOL DAUN TANAMAN SAMBUNG URAT (Cayratia carnosa) TERHADAP Salmonella thypi and Propionibacterium acnes - Inna, Mutma; Astuti, Winni; Saleh, Chairul (Jurusan Kimia FMIPA UNMUL, 2022)
This research was conducted to the content of secondary metabolite of methanol extract of Cayratia carnosa leaf and activity toward Salmonella thypi and Propionibacterium acnes. The phytochemical test has tested by color testing and antibacterial activity carried out by agar diffution method. The secondary metabolites contained in the methanol extract from the Cayratia carnosa leaf are Flavonoids, Steroid and phenolic. Methanol extract from Cayratia carnosa leaf has a wide range of action. The value of Minimun Inhibitory Concentracion (MIC) for methanol extracts from the Cayratia carnosa leaf toward Salmonella thypi is between 6 to 8% and Propionibacterium acnes between 0.5 to 1%. Keywords: Cayratia carnosa (Link) Gagnepain, Phytochemical test, Antibacterial activity.